Identification of Risk Factors Causing Stunting in Children Under Five Years of Age - Lindesi Yanti; Fermata Sari; Aris Teguh Hidayat; Masniati Arafah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting is a global health problem in children that has an impact on increasing morbidity and mortality, developmental disorders (cognitive, motor, language), and increasing the economic burden for the costs of child care and treatment.The aim is to identify risk factors for stunting in children under five years of age. The research method uses a descriptive observational design and a cross-sectional approach, with a sample size of 94 respondents use cluster sampling. Measuring instruments used Questionnaire which contains a history of exclusive breastfeeding, history of infectious diseases, immunization status and 10 knowledge questions about stunting that have been tested for validity. Correlation data analysis using chi-square, and multiple logistic regression prediction modeling. The results of the study showed a significant relationship between exclusive breastfeeding and the incidence of stunting in toddlers. Toddlers who do not receive exclusive breastfeeding have a 33.139 times greater chance of experiencing stunting compared to toddlers who receive exclusive breastfeeding with a wald value of 14.159. The conclusion is that the factor of exclusive breastfeeding is the factor that plays the most role in influencing the incidence of stunting in toddlers.An important role is needed for cadres, health promoters, and health services to support the government's program on providing exclusive breastfeeding, providing education and providing correct and accurate information regarding stunting and how to prevent it.